Dendrophorbium chopinii (Compositae: Senecioneae), a new species from Amazonas Region, Peru - Montesinos-Tubée, Daniel B. (Phytotaxa, 2017)
A new species of Dendrophorbium from northern Peru is described and illustrated. The species is, so far, only known from the type locality in southern Leimebamba Province (Amazonas Region, Peru). Morphological characters are provided in order to distinguish it from the closest relatives. A table with the morphological comparison with other species of Dendrophorbium is provided.